HAK-HAK KAUM BURUH JANGAN TERBLENGGU OLEH PEMASUNGAN KEPENTINGAN PEMILIK MODAL (Kepastian Hukum Lewat Undang-Undang Nomor: 13/2013 Tentang Ketenagakerjaan) - Ali Imron (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
Employment comes from the workforce, which in Article 1 paragraph 2 of Law No. 13 2003 Manpower is "Manpower is every person who is able to work in order to produce goods and / or services, both for subsistence and for the community." While understanding of labor in accordance with Article 1 paragraph 1 of Law No. 13 2003 Manpower is "Employment is everything related to the workforce at a time before, during, and after the work period." In order to improve the standard of living it is necessary to the development of various aspects. No exception to the manpower development is done on the principle of integration through functional coordination across sectors and regional center. In this case the intention is Ketanagakerjaan construction principle based on the principal of national development especially its principle of Pancasila democracy, the principle of fair and equitable.Keywords: Labor Rights, Own Capital